A Comparative Study On Factors Affecting Selection Of Online Vs Offline Shopping Of Regular Apparels (Cloths) Among Gen-Z In Ahmedabad City - Yash Dalsaniya; Rutva Sarvaiya (International Journal of Applied and Scientific Research, 2024)
This study investigates factors influencing Gen Z's choice of online and offline shopping for regular apparel in Ahmedabad, India. It examines determinants like product inspection, discounts, and preferences using a quantitative approach to analyse the relationship between age and shopping behaviour. The results show a weak link between age and shopping mode, with preferences shaped more by characteristics than age-specific differences. Gen Z appreciates online experiences like personalization and offline aspects like social interaction and product quality checks. Despite online shopping growth, physical stores remain essential for experimentation. Retailers and wholesalers should adopt hybrid strategies to meet Gen Z’s preferences. Future research is recommended to explore psychological and technological factors influencing Gen Z'sshopping behaviour